3. Proposals Regarding the Work Strategies in Plastic Visual Activities. The Professor as a Visual Art Mediator - Aprotosoaie-Ifti (Sciendo, 2017)
Starting from the cultural mediator model, the teacher, in his turn, can be positioned from the perspective of the assumed positioned of art mediator. Thus, his role would be to make art accessible to a public under training (students). Approaching activities in an upward direction - from the uninitiated (students) towards the professionals (artists), the designed activities will thus start from the developmental needs of the students. Finding ways of connecting youth and art by introducing art into everyday life and identifying examples where elements, skills and knowledge about art can be applied in everyday life and the permanent concentration of the mediator professor on the public/youth/students and not on the works of art and, thus placing young people at the heart of artistic mediation are several ways of opening, awakening and training the interest of the new art public.